2019
DOI: 10.2174/1573402114666180924143801
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Overnight Blood Pressure Dipping in Second Trimester; A Strong Predictor of Gestational Hypertension and Preeclampsia

Abstract: Background: Preeclampsia is a global burden with 10 million incidences annually and 210 daily deaths worldwide. Diagnosis is mainly based on the features following full presentation. Objective: This study explored whether early pregnancy circadian changes of ambulatory blood pressure monitoring (ABPM) could predict preeclampsia and hypertension. Methods: In a prospective study, 294 pregnant women who were referred to Sarem Women’s Hospital, Iran were recruited. Systolic, diastolic and mean arterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, it was found that pattern of daily changes in BP conveyed significant additional information about the severity of the disease and related complications. Disrupted dipping pattern was associated with renal end-organ damage [17], progression of coronary artery disease [18], cerebrovascular event risk [19] and hypertension-related complications in pregnancy [20]. As a result, wide clinical use and standardization of ambulatory blood pressure monitorization was rigorously proposed [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that pattern of daily changes in BP conveyed significant additional information about the severity of the disease and related complications. Disrupted dipping pattern was associated with renal end-organ damage [17], progression of coronary artery disease [18], cerebrovascular event risk [19] and hypertension-related complications in pregnancy [20]. As a result, wide clinical use and standardization of ambulatory blood pressure monitorization was rigorously proposed [21].…”
Section: Discussionmentioning
confidence: 99%
“…ScottCare software automatically scores BP readings and calculates average daytime and nighttime SBP and DBP, daytime and nighttime BP variability (i.e., the standard deviation of BP readings throughout a 24‐hr period), and BP dipping (i.e., a difference of more than 10% between mean daytime and nighttime BP). Loss of BP dipping is an early sign of preeclampsia (Saremi et al., 2019). ABPM was considered valid if 15 or more measurements were captured.…”
Section: Methodsmentioning
confidence: 99%
“…107 A strong association has been reported between attenuated dipping of BP at night during the second trimester and subsequent development of preeclampsia in the third trimester. 108…”
Section: Common Mechanisms Underlying Nondipping and Morning Bp Surgementioning
confidence: 99%